Assessment of peripapillary retinal nerve fiber layer thickness in school-aged myopic eyes using optical coherence tomography: A cross-sectional optical coherence tomography study - Tran, Nguyen Tra My; Nguyen, Thi Thu; Vo Tran, Vy Khanh (Tạp chí Y Dược Huế, 2026)
Background: Myopia is a major global health challenge, projected to affect 50% of the world population by 2050, with over 60% prevalence in Asian school-aged children. Assessment of peripapillary retinal nerve fiber layer (pRNFL) thickness using optical coherence tomography (OCT) provides critical insights into myopia-associated structural alterations. Objectives: To characterize refractive and biometric parameters, pRNFL in school-aged myopic children and identify factors associated with pRNFL. Materials and Methods: This cross-sectional study examined 123 eyes of 74 myopic children aged 6-18 years. Comprehensive ophthalmic evaluation included visual acuity, cycloplegic refraction, axial length measurement, and spectral-domain OCT for pRNFL quantification. Statistical analysis assessed correlations between pRNFL parameters, spherical equivalent refractive error (SE), and axial length. Results: Mean participant age was 11.46 ± 3.10 years, with mean SE of -3.35 ± 1.76 diopters and axial length of 24.92 ± 0.97 mm. Global mean pRNFL thickness was 102.75 ± 9.15 μm. Quadrant measurements showed superior 133.31 ± 18.59 μm, inferior 130.85 ± 15.25 μm, nasal 65.77 ± 13.07 μm, and temporal 81.11 ± 13.03 μm. Global pRNFL thickness demonstrated significant positive correlations with SE (p < 0.05) and negative correlations with axial length (p < 0.05). Conclusions: This study establishes normative pRNFL values for Vietnamese school-aged myopic patients, revealing significant correlations between pRNFL thickness, refractive error, and axial length, providing evidence-based clinical monitoring references.